2022
DOI: 10.1002/path.6020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the β2‐adrenergic receptor increases chemosensitivity in multiple myeloma by induction of apoptosis and modulating cancer cell metabolism

Abstract: While multi‐drug combinations and continuous treatment have become standard for multiple myeloma, the disease remains incurable. Repurposing drugs that are currently used for other indications could provide a novel approach to improve the therapeutic efficacy of standard multiple myeloma treatments. Here, we assessed the anti‐tumor effects of cardiac drugs called β‐blockers as a single agent and in combination with commonly used anti‐myeloma therapies. Expression of the β2‐adrenergic receptor correlated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…At present, multi‐drug combination chemotherapy is still the main first‐line treatment option for this disease. Compared with single drug therapy, the efficacy of multi‐drug combination therapy is increased, but at the same time, the adverse effects are also increased 13 . Therefore, it is particularly important to seek for new therapeutic means to increase the treatment efficacy and improve the life quality of MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…At present, multi‐drug combination chemotherapy is still the main first‐line treatment option for this disease. Compared with single drug therapy, the efficacy of multi‐drug combination therapy is increased, but at the same time, the adverse effects are also increased 13 . Therefore, it is particularly important to seek for new therapeutic means to increase the treatment efficacy and improve the life quality of MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study illustrated the possibility of using BBs as a supplementary therapy as it induces cell cycle arrest and promote apoptosis in human colorectal cancer cells ( Coelho et al, 2015 ). As of 2023, a new study demonstrated that the concurrent use of PRO with chemotherapy, exhibits antitumor properties when administered alongside chemotherapy in the context of multiple myeloma cells ( Satilmis et al, 2023 ).…”
Section: Improving the Effectiveness Of Cancer Treatment: The Synergi...mentioning
confidence: 99%
“…Furthermore, another study aimed to assess the antitumor effects of NSBB and SBB in multiple myeloma when combined with chemotherapy. It was concluded that BBs that targets β2-AR from PRO to ICI affected multiple myeloma cell viability and induced apoptosis and autophagy ( Satilmis et al, 2023 ).…”
Section: Non-selective Beta Blockers Vs Selective Beta Blockers (Nsbb...mentioning
confidence: 99%
See 1 more Smart Citation
“…These fibers release norepinephrine that will bind to the β2 adrenergic receptor (β2AR), found on the different cell types in the BM [ 105 ]. We found that β2AR is a poor prognostic factor in MM and that the β2AR blocker propranolol inhibited mTOR activation which led to increased apoptosis in MM cells [ 106 ].…”
Section: Introductionmentioning
confidence: 99%